Retraction of the main papilla toward the biliary system in patients with primary sclerosing cholangitis - Parlak, Erkan; Köksal, Aydın Şeref; Dişibeyaz, Selçuk; Çiçek, Bahattin; Ödemiş, Bülent; Şaşmaz, Nurgül; Şahin, Burhan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Retraction of the main papilla toward the biliary system was observed in 70% of patients with primary sclerosing cholangitis (PSC). However, this observation was confounded by the fact that all of the patients with this finding had a prior history of sphincterotomy. The aim of the present study was to observe whether main papillary retraction can be seen in patients with naïve papillae and accompanies the progression of the disease. Materials and Methods: The study was conducted in a single tertiary reference center and included 4 patients with PSC. Results: Main papillary retraction was seen to emerge with progression of PSC after an initial presentation with intra and extrahepatic involvement in 2 patients and after progression from intrahepatic to extrahepatic bile ducts in 1 patient. Main papillary retraction was seen in 2 patients with naïve papillae and could be detected by magnetic resonance cholangiography in 1 patient. Conclusion: Retraction of the main papilla can be seen in patients with PSC regardless of prior sphincterotomy history.